ANALISIS PENGARUH KESADARAN, KUALITAS PELAYANAN PAJAK DAN SANKSI PAJAK TERHADAP TIGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA DEPOK SAWANGAN - Mulia Rahmah, S. Kom., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
This study aims to determine the Analysis of the Influence of Tax Services, and Tax Sanctions on the Level of Personal Taxpayer Compliance at the Depok Sawangan Pratama Tax Office. The population in this research is quantitative research with a descriptive approach. Research Result.The results of this study indicate that the variable influence of awareness, quality of tax services and tax sanctions on the level of compliance of individual tax payer. This can be proven Tax Awareness obtains a value of arithmetic of 3,511 which is greater than the value of tabel of 1,98498 a significant value of 0,001 means less than 0,05 so it can be concluded that tax awareness has a positive effect on tax compliance. The Tax Service Quality varibale obtains the t value of 2,411 which means it is greater than the t table value of 1,98498, a significant value of 0,032 which means it is less than 0,05 so it can be concluded that the Tax Service Quality has a positive effect on tax compliance. The Tax Sanction variable obtained a t value of 2,174 which means it os greater than the table value of 1,98498 a significant value of 0,043 which means less than 0,05 so it can be concluded that tax sanctions have a positive effect on tax compliance.Based on the results og the study conclued that the variabel Analysis of Awareness, Quality of Tax Service, and Tax Sanctions on the Level of Compliance of Individual Taxpayers in Depok Sawangan Pratama Tax Office. Sanctions Author Depok Sawangan Primary Tax Office to hold regular and on going socialization about tax payer awareness that contains the benefits of paying tax payers and corporate tax payer can be more obedient in fulfilling obligations and paying their taxes so that it will have an impact on increasing tax revenue in Indonesia.